Development of a postgraduate programme on play - Ferreira, Isabel (2023)
On the academic year 22.23 the post-Graduate programme on “Play” started with a cohort of 16 students, composed of occupational therapy practitioners who range between 30 to 2 years of professional experience leading to an average of 13 years of clinical practice. Their working environment ranges within community, hospital and private practice settings. Nonetheless the programme planning and set up started in the academic year 21.22, being this then the 1st edition. Future editions are planned, with the mindset of continuing update, not only based on the previous experiences, users feedback (students and teachers) and also on the state-of-the art on Play as well the innovation within educational practices. This programme was grounded in a blended learning format, with diversity in the geographical distribution of teachers, across the globe, as well as students, within Portugal. This Post-Graduate programme is organised in curricular units, which some can also be attended by other professionals of the education, health, and social arena, considering the evidence-based fact that the approach to the child and its occupation, specifically here Play, is a multidisciplinary matter. These curricular units range from Occupational Science to specific Play theory models and Parenthood. The learning outcomes topics include specialized clinical reasoning within the most updated evidence-based theoretical-practical knowledge on Play, the occupational and contextual domains that influence Play, the uniqueness and specificity of the Play Occupational Therapy approach, assessment instruments and intervention models and effective communication and interaction for the different interdisciplinary connection points regarding Play. Ultimately, this programme aims to approach Play within the child centered perspective, based on its preferences, needs and participation/engagement which directly relates to the stated on General comment No. 17 (2013) on the right of the child to rest, leisure, play, recreational activities, cultural life and the arts (art. 31), which clearly and unequivocally mentions “Research evidence highlights that playing is also central to children’s spontaneous drive for development, and that it performs a significant role in the development of the brain, particularly in the early years.” Hence considering as stated also that “Play and recreation are essential to the health and well-being of children and promote the development of creativity, imagination, self-confidence, self efficacy, as well as physical, social, cognitive and emotional strength and skills - They contribute to all aspects of learning” it is aimed that this programme contributes to the research and knowledge development within Occupational Therapy Service Provision.